Monolithic catalyst containing titanium silicalite molecular sieve coating as well as preparation method and application of monolithic catalyst
By using a monolithic catalyst containing titanium silicon molecular sieve coating in petrochemical production, the existing catalysts have solved the problems of high amount, high cost and poor stability, and have achieved efficient, cheap and environmentally friendly catalytic effects, and are suitable for high aerial speed and atmospheric gas treatment conditions.
Patent Information
- Application Number
- CN202311165076.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-11
AI Technical Summary
When existing catalysts are used to treat carbon-based oxygen-containing molecular gases in petrochemical production, there are problems such as high usage of precious metals, high cost and poor stability, and it is difficult to achieve efficient, cheap and environmentally friendly catalytic effects.
The monolithic catalyst is used to coat titanium silicon molecular sieve, which consists of an acid-treated regular support, a titanium silicon molecular sieve coating and active components dispersed in the coating, which contains precious metals and optional alloy metals. The coating is formed by crystallization-self-growth, which improves the firmness of the coating and the dispersion of the active precious metals.
It has achieved efficient removal of carbon-based oxygen-containing molecular gases, improved catalytic oxidation efficiency, reduced the content of precious metal components, reduced operating costs, and has good mechanical strength and water resistance, which is suitable for high-speed and atmospheric gas treatment conditions.
Smart Images

Figure CN119588412A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to an integral catalyst containing a titanium silicon molecular sieve coating, and a preparation method and application thereof. Background Art
[0002] In the petrochemical production process, carbon-based energy small molecules often undergo incomplete reactions during the directional oxidation process, resulting in the enrichment of oxygen-containing small molecule gases in the exhaust gas discharged from the device or the circulating carrier gas, which not only causes the risk of explosion in the chemical production process, but also forms photochemical phenomena, causing pollution to the surrounding environment. At present, the main treatment method for oxygen-containing small molecule exhaust gas discharged from the oxidation process of petrochemical devices is catalytic oxidation. Catalytic oxidation can completely oxidize oxygen-containing small molecule gases to form carbon dioxide. At the same time, in order to meet the requirements of low pressure drop and large air volume conditions, the current catalytic oxidation method generally uses a monolithic catalyst loaded with precious metals. However, the problems of large amount of precious metals, high cost and poor stability still exist.
[0003] Patent application CN102481549B discloses a Pt-Ru dual-active component, a monolithic catalyst with a coating of a Ce-Cr solid solution and an aqueous mixture of tin oxide and a honeycomb ceramic as a substrate, which is used to destroy CO and volatile organic compounds emitted in logistics. However, the monolithic catalyst needs to be loaded with a large amount of platinum group precious metals during the preparation process, and low specific surface area colloidal silica and titanium oxide binders are added during the preparation of the monolithic catalyst, resulting in poor dispersion when the precious metals are loaded and low effective utilization rate.
[0004] Patent application CN111036289A discloses a catalyst having a regular structure in which the matrix slurry component is a titanium silicon molecular sieve modified with a noble metal. However, the catalyst needs to be prepared using a nano-titanium sol modified with a silane coupling agent, which has a high preparation cost and an unclear prospect for industrial promotion.
[0005] Patent application CN1986035A discloses a method for purifying automobile exhaust. The catalyst can purify CO, HC, and NOx at a relatively low ignition temperature, but more precious metals are required to achieve the expected purification target, and the active components will fall off the carrier after a period of use.
[0006] Patent application CN1488435A discloses a catalytic combustion catalyst and a preparation method thereof. The catalyst has a high catalytic combustion conversion efficiency of organic waste gas, but requires the use of a high content of precious metal elements and has the disadvantages of being expensive, having poor anti-toxicity and poor general applicability.
[0007] Patent application CN101138728A relates to a catalyst for purifying a metal oxide mixture for purifying organic waste gas and a method for preparing the same. The method comprises loading an activated alumina coating modified with a cerium lanthanum zirconium mixed oxide and an active component containing a mixture of multiple metal oxides on a cordierite carrier at one time. The catalyst has the characteristics of high catalytic efficiency, simple preparation, low cost and easy promotion. However, the catalyst is easily reduced and deactivated by reducing gas (CO) in industrial waste gas.
[0008] Therefore, the development of highly efficient, inexpensive, environmentally friendly, and durable catalysts has become a research hotspot and application trend of catalytic oxidation catalysts at home and abroad. Summary of the invention
[0009] The purpose of the present invention is to efficiently remove carbon-based oxygen-containing molecular gases from tail gas discharged during petrochemical production processes, and to provide an integral catalyst containing a titanium silicon molecular sieve coating, a preparation method and an application thereof.
[0010] In order to achieve the above object, the present invention provides a monolithic catalyst containing a titanium silicon molecular sieve coating, the monolithic catalyst comprising:
[0011] A carrier, wherein the carrier is a regular carrier treated with acid;
[0012] A coating layer attached to the carrier, wherein the coating layer is a titanium silicon molecular sieve; and
[0013] an active component dispersed in the coating, the active component comprising a noble metal and optionally an alloying metal;
[0014] The powder loss rate of the coating is below 1%, preferably 0.1-1%, and more preferably 0.1-0.5%.
[0015] Preferably, the particle size of the coating is 50-500 nm.
[0016] Preferably, the mesoporous channel size of the coating is 1-50 nm, and the specific surface area is 300-600 m 2 / g.
[0017] Preferably, relative to 100 parts by weight of the carrier, the content of the coating layer is 1-10 parts by weight, and the content of the active component is 0.1-1 part by weight.
[0018] Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
[0019] Preferably, in the active component, the molar ratio of the noble metal to the alloy metal is 1:0.1-0.3.
[0020] Preferably, the noble metal is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium.
[0021] Preferably, the alloy metal is at least one of Fe, La and Ce, preferably a combination of La and Ce.
[0022] Preferably, the titanium silicate molecular sieve is TS-1 molecular sieve.
[0023] The second aspect of the present invention provides a method for preparing a monolithic catalyst containing a titanium silicon molecular sieve coating, the method comprising the following steps:
[0024] (1) treating the structured support with acid;
[0025] (2) mixing the alcohol solution of the titanium source with the aqueous solution containing the microporous template and the silicon source, aging, removing the alcohol, and then mixing the obtained gel solution with titanium silicon molecular sieve seed crystals and the mesoporous template to obtain a coating slurry;
[0026] (3) adding the coating slurry to the acid-treated regular carrier, followed by crystallization, washing, drying and calcination to obtain a carrier containing the coating;
[0027] (4) impregnating the coated support into a mixed solution containing a noble metal precursor and an optional structural additive, and then sequentially drying, calcining and reducing the impregnated catalyst precursor.
[0028] Preferably, in step (1), the acid treatment process comprises: subjecting the structured carrier to a reflux treatment with an acidic solution, and then washing it to neutrality and drying it.
[0029] Preferably, the concentration of the acidic solution is 1-3 mol / L.
[0030] Preferably, the acid in the acidic solution is at least one of nitric acid, sulfuric acid and hydrochloric acid.
[0031] Preferably, the reflux treatment conditions include: a temperature of 70-90° C. and a time of 12-36 hours.
[0032] Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
[0033] Preferably, in step (2), the specific process of mixing the alcohol solution of the titanium source with the aqueous solution containing the microporous template and the silicon source is: adding the alcohol solution of the titanium source to the aqueous solution containing the microporous template and the silicon source at a rate of 0.005-0.015 mL / min, and stirring and mixing for 2-5 hours.
[0034] Preferably, the titanium source is selected from at least one of tetraalkoxytitanium, tetraalkyl titanate and titanium tetrachloride.
[0035] Preferably, the microporous template agent is selected from at least one of tetrapropylammonium hydroxide, tetrapropylammonium bromide and tetraethylammonium hydroxide.
[0036] Preferably, the silicon source is selected from at least one of silicates, silicic acid, silica hydrogel and tetraethyl orthosilicate.
[0037] Preferably, the titanium silicon molecular sieve seed crystals are TS-1 molecular sieve seed crystals.
[0038] Preferably, the mesoporous template agent is selected from at least one of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), CTAB (hexadecyltrimethylammonium bromide) and n-butylamine.
[0039] Preferably, in step (3), the crystallization conditions include: temperature of 150-200° C. and time of 10-72 h.
[0040] Preferably, the calcination conditions include: a temperature of 400-650° C. and a time of 4-10 hours.
[0041] Preferably, in step (4), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12.
[0042] Preferably, the noble metal precursor is selected from at least one of chloroplatinic acid, 2-hydroxyethylamine hexahydroxoplatinic acid (IV), platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
[0043] Preferably, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide.
[0044] Preferably, the calcination conditions include: a temperature of 300-400° C. and a time of 4-10 hours.
[0045] Preferably, during the reduction process, the reducing atmosphere is H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations.
[0046] Preferably, the reduction conditions include: catalyst heating rate of 2-20°C / min, reduction temperature of 300-450°C, and reduction time of 1-10h.
[0047] The third aspect of the present invention provides a monolithic catalyst containing a titanium silicon molecular sieve coating prepared by the above method.
[0048] The fourth aspect of the present invention provides the use of the above-mentioned monolithic catalyst containing titanium silicon molecular sieve coating in catalytic oxidation of carbon-based oxygen-containing molecular gas.
[0049] According to the technical scheme of the present invention, in the process of preparing the catalyst, by treating the structured carrier with acid and then attaching the titanium silicon molecular sieve coating, the titanium silicon molecular sieve can react with the exposed hydroxyl groups on the surface of the structured carrier after the acid treatment, and a chemical bond is formed between the coating and the structured carrier, so that the titanium silicon molecular sieve coating has high firmness and extremely low powder loss rate; and, the titanium silicon molecular sieve coating is formed by a crystallization-self-growth method, which can promote the dispersion of active precious metals and the exposure of active phases, efficiently construct catalytic active sites on the catalyst surface, and while reducing the content of active precious metal components, it can increase the adsorption capacity of carbon-based oxygen-containing molecular gases and oxygen, promote the adsorption and activation of oxygen, and thus improve the catalytic efficiency of the catalyst.
[0050] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0051] (1) The monolithic catalyst containing titanium silicon molecular sieve coating prepared by the present invention has high oxygen adsorption and activation capabilities and high catalytic oxidation efficiency;
[0052] (2) The monolithic catalyst containing titanium silicon molecular sieve coating prepared by the present invention has high mechanical strength and is suitable for high space velocity and large volume gas treatment conditions;
[0053] (3) In the monolithic catalyst containing titanium silicon molecular sieve coating of the present invention, the titanium silicon molecular sieve coating and the carrier are chemically bonded, which has the advantages of high firmness, strong water resistance, and is conducive to continuous long-term operation;
[0054] (4) The content of active precious metal components in the monolithic catalyst containing titanium silicon molecular sieve coating prepared by the present invention is relatively low, which can greatly reduce the operating cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 is a SEM image of the monolithic catalyst containing TS-1 molecular sieve coating prepared in Example 1;
[0056] Figure 2 This is a TEM image of the monolithic catalyst containing the TS-1 molecular sieve coating prepared in Example 1. DETAILED DESCRIPTION
[0057] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0058] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0059] In the present invention, unless otherwise specified, the concentration "%" of a gas refers to "volume %"; the "space velocity" refers to "volume space velocity"; and the pressure refers to absolute pressure.
[0060] The monolithic catalyst containing titanium silicon molecular sieve coating of the present invention comprises:
[0061] A carrier, wherein the carrier is a regular carrier treated with acid;
[0062] A coating layer attached to the carrier, wherein the coating layer is a titanium silicon molecular sieve; and
[0063] An active component is dispersed in the coating, the active component comprising a noble metal and optionally an alloying metal.
[0064] In the monolithic catalyst containing titanium silicon molecular sieve coating of the present invention, there is a strong bonding strength between the coating and the regular carrier. Specifically, the powder loss rate of the coating is less than 1%, preferably 0.1-1%, and more preferably 0.1-0.5%. In the present invention, the powder loss rate is detected by ultrasonic oscillation method, and the detection conditions include: ultrasonic frequency 45kHz, ultrasonic power 130W, and treatment time 60min.
[0065] In a specific embodiment, the carrier containing titanium silicon molecular sieve coating is prepared according to the following method:
[0066] (1) treating the structured support with acid;
[0067] (2) mixing the alcohol solution of the titanium source with the aqueous solution containing the microporous template and the silicon source, aging, removing the alcohol, and then mixing the obtained gel solution with titanium silicon molecular sieve seed crystals and the mesoporous template to obtain a coating slurry;
[0068] (3) Adding the coating slurry to the acid-treated regular carrier, followed by crystallization, washing, drying and calcination in sequence to obtain a carrier containing titanium silicon molecular sieve coating.
[0069] In the above preparation process, a titanium silicon molecular sieve coating is formed on the regular carrier by carrier acid treatment and crystallization-self-growth. A chemical bond is formed between the titanium silicon molecular sieve coating and the regular carrier, so the titanium silicon molecular sieve coating has high firmness and extremely low powder loss rate.
[0070] In the monolithic catalyst containing titanium silicon molecular sieve coating of the present invention, the particle size of the coating may be 50-500 nm, preferably 80-480 nm.
[0071] In the monolithic catalyst containing titanium silicon molecular sieve coating of the present invention, the mesopore size of the coating can be 1-50nm, preferably 1.7-45nm; the specific surface area can be 300-600m 2 / g, preferably 400-550m 2 / g.
[0072] In the monolithic catalyst containing titanium silicon molecular sieve coating described in the present invention, the content of the coating can be 1-10 parts by weight, specifically, for example, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight or 10 parts by weight, relative to 100 parts by weight of the carrier; the content of the active component can be 0.1-1 part by weight, specifically, for example, 0.1 part by weight, 0.2 part by weight, 0.3 part by weight, 0.4 part by weight, 0.5 part by weight, 0.6 part by weight, 0.7 part by weight, 0.8 part by weight, 0.9 part by weight or 1 part by weight.
[0073] In the present invention, the structured carrier is preferably selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier, and the most preferred one is a cordierite honeycomb carrier.
[0074] In the present invention, the titanium silicate molecular sieve forming the titanium silicate molecular sieve coating can be various conventional mesoporous titanium silicate molecular sieves. In the most preferred embodiment, the titanium silicate molecular sieve is TS-1 molecular sieve.
[0075] In the monolithic catalyst containing titanium silicon molecular sieve coating of the present invention, in the active component, the alloy metal is an optional component. In a more preferred embodiment, the active component contains noble metal and alloy metal. In this preferred embodiment, the active component exists in the form of noble metal element, alloy and noble metal oxide. In the active component, the molar ratio of the noble metal to the alloy metal can be 1:0.1-0.3, preferably 1:0.15-0.2.
[0076] In the monolithic catalyst containing titanium silicon molecular sieve coating of the present invention, in the active component, the noble metal can be selected from at least one of ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium. When the noble metal is a combination of platinum and palladium, the molar ratio of platinum to palladium can be 1:0.5-2, and most preferably 1:1.
[0077] In the monolithic catalyst containing titanium silicon molecular sieve coating of the present invention, in the active component, the alloy metal can be at least one of Fe, La and Ce, preferably a combination of La and Ce. When the alloy metal is a combination of La and Ce, the molar ratio of La to Ce can be 1:0.5-2, and most preferably 1:1.
[0078] The method for preparing the monolithic catalyst containing titanium silicon molecular sieve coating of the present invention comprises the following steps:
[0079] (1) treating the structured support with acid;
[0080] (2) mixing the alcohol solution of the titanium source with the aqueous solution containing the microporous template and the silicon source, aging, removing the alcohol, and then mixing the obtained gel solution with titanium silicon molecular sieve seed crystals and the mesoporous template to obtain a coating slurry;
[0081] (3) adding the coating slurry to the acid-treated regular carrier, followed by crystallization, washing, drying and calcination to obtain a carrier containing the coating;
[0082] (4) impregnating the coated support into a mixed solution containing a noble metal precursor and an optional structural additive, and then sequentially drying, calcining and reducing the impregnated catalyst precursor.
[0083] In step (1), the acid treatment process may include: refluxing the structured carrier with an acidic solution, then washing it to neutrality and drying it.
[0084] Specifically, the concentration of the acidic solution may be 1-3 mol / L, preferably 1.5-2.5 mol / L, and most preferably 2 mol / L.
[0085] Specifically, the acid in the acidic solution may be an inorganic strong acid, preferably at least one of nitric acid, sulfuric acid and hydrochloric acid.
[0086] Specifically, the reflux treatment conditions may include: a temperature of 70-90° C., preferably 80° C.; and a time of 12-36 hours, preferably 24 hours.
[0087] In the method of the present invention, the structured carrier can be selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier, preferably a cordierite honeycomb carrier. In a specific embodiment, the structured carrier is a cordierite honeycomb ceramic.
[0088] In step (2), the specific process of mixing the alcohol solution of the titanium source with the aqueous solution containing the microporous template and the silicon source is: adding the alcohol solution of the titanium source to the aqueous solution containing the microporous template and the silicon source at a rate of 0.005-0.015 mL / min, and stirring and mixing for 2-5 hours.
[0089] In the present invention, the titanium source can be selected from water-soluble or water-soluble titanium-containing compounds, generally referring to titanium dioxide (TiO2) sources. In a specific embodiment, the titanium source includes but is not limited to at least one of tetraalkoxy titanium, tetraalkyl titanate and titanium tetrachloride, and n-butyl titanate is most preferred.
[0090] In the present invention, in the alcohol solution of the titanium source, the alcohol solvent used may be at least one of isopropanol, ethanol and n-propanol.
[0091] In the present invention, the concentration of the alcohol solution of the titanium source may be 5-15% by weight.
[0092] In the present invention, the silicon source can be selected from water-soluble or water-soluble silicon-containing compounds, generally referring to a silicon dioxide (SiO2) source. In a specific embodiment, the silicon source includes but is not limited to at least one of silicate, silicic acid, silica hydrogel and tetraethyl orthosilicate, preferably tetraethyl orthosilicate.
[0093] In the present invention, the microporous template agent may be selected from at least one of tetrapropylammonium hydroxide, tetrapropylammonium bromide and tetraethylammonium hydroxide.
[0094] In the present invention, the titanium silicate molecular sieve seed crystal is preferably a TS-1 molecular sieve seed crystal.
[0095] In the present invention, the mesoporous template agent may be selected from at least one of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), CTAB (hexadecyltrimethylammonium bromide) and n-butylamine.
[0096] In step (2), the aging process can be carried out at room temperature for 2-5 hours.
[0097] In step (2), the alcohol removal process is specifically as follows: heating the aged mixed solution to 85-95°C at a rate of 1-20°C / min (preferably 5-17°C / min), and removing alcohol at 85-95°C for 10-15 hours.
[0098] In step (2), the process of mixing the gel solution with the titanium silicalite seed crystals and the mesoporous template is carried out under stirring. The mixing conditions may include: a temperature of 35-45° C. and a time of 0.5-2 hours.
[0099] In step (3), the process of adding the coating slurry to the acid-treated structured carrier is specifically as follows: slowly dropping the coating slurry into the acid-treated structured carrier.
[0100] In step (3), the crystallization conditions may include: a temperature of 150-200° C. and a time of 10-72 h.
[0101] In step (3), the calcination conditions include: a temperature of 400-650° C., preferably 500-600° C.; and a calcination time of 4-10 hours.
[0102] In step (4), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12.
[0103] In the present invention, the noble metal in the noble metal precursor is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium. In a specific embodiment, the noble metal precursor is selected from at least one of chloroplatinic acid, hexahydrooxoplatinic acid (IV) 2-hydroxyethylamine salt, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
[0104] In the present invention, the structural additive is added to provide alloy metals so that the active components in the prepared monolithic catalyst exist in the form of noble metal elements, alloys and noble metal oxides. In a specific embodiment, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide.
[0105] In step (4), the calcination conditions may include: a temperature of 300-400° C. and a time of 4-10 hours.
[0106] In step (4), during the reduction process, the reducing atmosphere may be H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations. In a specific embodiment, the reducing atmosphere is a mixed atmosphere of different H2 concentrations or different CO concentrations, and the formation of surface oxygen vacancies of the catalyst is efficiently controlled by regulating the reducing atmosphere. Specifically, the reducing atmosphere may be 5% H2 (N2 dilution), 10% H2 (N2 dilution), 15% H2 (N2 dilution), 5% CO (N2 dilution), etc.
[0107] In step (4), the reduction conditions may include: a catalyst heating rate of 2-20° C. / min, a reduction temperature of 300-450° C., and a reduction time of 1-10 h.
[0108] In the method described in the present invention, the amounts of various reaction raw materials used in steps (1) to (4) are such that in the prepared integral catalyst containing titanium silicon molecular sieve coating, the content of the coating is 1-10 parts by weight, preferably 2-8 parts by weight, relative to 100 parts by weight of the carrier; and the content of the active component is 0.1-1 part by weight, preferably 0.1-0.5 part by weight.
[0109] The present invention also provides an integral catalyst containing titanium silicon molecular sieve coating prepared by the above method.
[0110] The present invention also provides the use of the above-mentioned integral catalyst containing titanium silicon molecular sieve coating in catalytic oxidation of carbon-based oxygen-containing molecular gas.
[0111] The following examples further illustrate the monolithic catalyst containing titanium silicon molecular sieve coating and its preparation method and application. The examples are implemented on the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.
[0112] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0113] Example 1
[0114] This example is used to illustrate the monolithic catalyst containing TS-1 molecular sieve coating and its preparation method and application.
[0115] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0116] Secondly, 3.6 g of isopropanol and 0.368 g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9 g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58 g of ethyl orthosilicate and 6.9 g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01 ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. The transparent gel liquid 4 was mixed with 1 g of commercially available TS-1 seed crystals and 0.5 g of P123 at 40°C and stirred for 1 h to obtain a coating slurry. The coating slurry was then added dropwise to the acid-treated cordierite honeycomb ceramics, transferred to an autoclave, and crystallized at 170°C for 36 h. After being taken out, washed and dried, it was calcined in an air atmosphere at 550°C for 6 hours to obtain a cordierite honeycomb ceramic containing a TS-1 molecular sieve coating.
[0117] Take 0.5L 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) and stir for 3h at 25℃, pH=9 to obtain active component solution 5. The cordierite honeycomb ceramic containing TS-1 molecular sieve coating is immersed in active component solution 5, let stand for 30min, take out the catalyst and blow it with 2MPa air knife, then treat it in a 100℃ oven for 12 hours, and calcine it at 250℃ for 6 hours. Then reduce it at 400℃ for 5 hours in 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst containing TS-1 titanium silicon molecular sieve coating. Among them, the coating particle size is between 80-150nm, the mesopore channel size distribution is 3-4nm, and the specific surface area is 550m 2 / g, and the powder loss rate of the coating is 0.1%.
[0118] The SEM and TEM images of the monolithic catalyst containing the TS-1 titanium silicon molecular sieve coating are shown in Figures 1 and 2. Figure 1 and Figure 2 shown.
[0119] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 265℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0120] Example 2
[0121] This example is used to illustrate the monolithic catalyst containing TS-1 molecular sieve coating and its preparation method and application.
[0122] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L sulfuric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0123] Secondly, 3.6 g of isopropanol and 0.368 g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9 g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58 g of ethyl orthosilicate and 6.9 g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01 ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 10-12°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. The transparent gel liquid 4 was mixed with 2 g of commercially available TS-1 seed crystals and 0.5 g of CTAB at 40°C and stirred for 1 h to obtain a coating slurry, which was then dropped into the acid-treated cordierite honeycomb ceramics and transferred to an autoclave for crystallization at 170°C for 36 h. After being taken out, washed and dried, the resultant was calcined at 550°C in an air atmosphere for 6 hours to obtain a cordierite honeycomb ceramic containing a TS-1 molecular sieve coating.
[0124] Take 0.5L 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) and stir for 3h at 25℃, pH=10 to obtain active component solution 5. The cordierite honeycomb ceramic containing TS-1 molecular sieve coating is immersed in active component solution 5, let stand for 30min, take out the catalyst and blow it with 2MPa air knife, then treat it in a 100℃ oven for 12 hours, and calcine it at 350℃ for 6 hours. Then reduce it at 400℃ for 5 hours in 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst containing TS-1 titanium silicon molecular sieve coating. Among them, the coating particle size is between 150-200nm, the mesopore channel size distribution is 1.7-45nm, and the specific surface area is 450m 2 / g, and the powder loss rate of the coating is 0.3%.
[0125] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1, reaction pressure 0.1MPa, reaction temperature 285℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 400h (i.e., the reaction was carried out continuously for 400h, and the catalytic activity of the catalyst did not decrease significantly).
[0126] Example 3
[0127] This example is used to illustrate the monolithic catalyst containing TS-1 molecular sieve coating and its preparation method and application.
[0128] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L hydrochloric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0129] Secondly, 3.6 g of isopropanol and 0.368 g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9 g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58 g of ethyl orthosilicate and 6.9 g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01 ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 15-17°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. The transparent gel liquid 4 was mixed with 1 g of commercially available TS-1 seed crystals and 1 g of n-butylamine at 40°C and stirred for 1 h to obtain a coating slurry. The coating slurry was then added dropwise to the acid-treated cordierite honeycomb ceramics, transferred to an autoclave, and crystallized at 170°C for 36 h. After being taken out, washed and dried, the mixture was calcined at 550°C in an air atmosphere for 6 hours to obtain a cordierite honeycomb ceramic containing a TS-1 molecular sieve coating.
[0130] Take 0.5L 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) and stir for 3h at 25℃, pH=11 to obtain active component solution 5. The cordierite honeycomb ceramic containing TS-1 molecular sieve coating is immersed in active component solution 5, let stand for 30min, take out the catalyst and blow it with 2MPa air knife, then treat it in a 100℃ oven for 12 hours, and calcine it at 450℃ for 6 hours. Then reduce it at 400℃ for 5 hours in 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst containing TS-1 titanium silicon molecular sieve coating. Among them, the coating particle size is between 300-450nm, the mesopore channel size distribution is 1.7-45nm, and the specific surface area is 350m 2 / g, and the powder loss rate of the coating is 0.5%.
[0131] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 305℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 300h (i.e., the reaction was carried out continuously for 300h, and the catalytic activity of the catalyst did not decrease significantly).
[0132] Example 4
[0133] This example is used to illustrate the monolithic catalyst containing TS-1 molecular sieve coating and its preparation method and application.
[0134] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 1 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0135] Secondly, 3.6 g of isopropanol and 0.368 g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9 g of tetrapropylammonium hydroxide was placed in a beaker, and 45.16 g of ethyl orthosilicate and 6.9 g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01 ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. The transparent gel liquid 4 was mixed with 1 g of commercially available TS-1 seed crystals and 0.5 g of P123 at 40°C and stirred for 1 h to obtain a coating slurry. The coating slurry was then added dropwise to the acid-treated cordierite honeycomb ceramics, transferred to an autoclave, and crystallized at 170°C for 36 h. After being taken out, washed and dried, it was calcined in an air atmosphere at 550°C for 6 hours to obtain a cordierite honeycomb ceramic containing a TS-1 molecular sieve coating.
[0136] Take 0.5L 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) and stir for 3h at 25℃, pH=9 to obtain active component solution 5. The cordierite honeycomb ceramic containing TS-1 molecular sieve coating is immersed in active component solution 5, let stand for 30min, take out the catalyst and blow it with 2MPa air knife, then treat it in a 100℃ oven for 12 hours, and calcine it at 250℃ for 6 hours. Then reduce it at 400℃ for 5 hours in 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst containing TS-1 titanium silicon molecular sieve coating. Among them, the coating particle size is between 100-350nm, the mesopore channel size distribution is 3-4nm, and the specific surface area is 350m 2 / g, and the powder loss rate of the coating is 0.5%.
[0137] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 280℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 300h (i.e., the reaction was carried out continuously for 300h, and the catalytic activity of the catalyst did not decrease significantly).
[0138] Example 5
[0139] This example is used to illustrate the monolithic catalyst containing TS-1 molecular sieve coating and its preparation method and application.
[0140] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0141] Secondly, 3.6 g of isopropanol and 0.368 g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9 g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58 g of ethyl orthosilicate and 6.9 g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.1 ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a heating rate of 20-30°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. The transparent gel liquid 4 was mixed with 1 g of commercially available TS-1 seed crystals and 0.5 g of P123 at 40°C and stirred for 1 h to obtain a coating slurry. The coating slurry was then added dropwise to the acid-treated cordierite honeycomb ceramics, transferred to an autoclave, and crystallized at 170°C for 36 h. After being taken out, washed and dried, it was calcined in an air atmosphere at 550°C for 6 hours to obtain a cordierite honeycomb ceramic containing a TS-1 molecular sieve coating.
[0142] Take 0.5L 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) and stir for 3h at 25℃, pH=9 to obtain active component solution 5. The cordierite honeycomb ceramic containing TS-1 molecular sieve coating is immersed in active component solution 5, let stand for 30min, take out the catalyst and blow it with 2MPa air knife, then treat it in a 100℃ oven for 12 hours, and calcine it at 250℃ for 6 hours. Then reduce it at 400℃ for 5 hours in 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst containing TS-1 titanium silicon molecular sieve coating. Among them, the coating particle size is between 280-350nm, the mesopore channel size distribution is 10-14nm, and the specific surface area is 370m 2 / g, and the powder loss rate of the coating is 0.6%.
[0143] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 265℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 270h (i.e., the reaction was carried out continuously for 270h, and the catalytic activity of the catalyst did not decrease significantly).
[0144] Example 6
[0145] This example is used to illustrate the monolithic catalyst containing TS-1 molecular sieve coating and its preparation method and application.
[0146] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0147] Secondly, 3.6 g of isopropanol and 0.368 g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9 g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58 g of ethyl orthosilicate and 6.9 g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01 ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. The transparent gel liquid 4 was mixed with 1 g of commercially available TS-1 seed crystals and 1.5 g of CTAB at 80°C and stirred for 1 h to obtain a coating slurry. The coating slurry was then added dropwise to the acid-treated cordierite honeycomb ceramics, transferred to an autoclave, and crystallized at 180°C for 48 h. After being taken out, washed and dried, it was calcined at 550°C in an air atmosphere for 6 hours to obtain a cordierite honeycomb ceramic containing a TS-1 molecular sieve coating.
[0148] Take 0.5L 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) and stir for 3h at 25℃, pH=9 to obtain active component solution 5. The cordierite honeycomb ceramic containing TS-1 molecular sieve coating is immersed in active component solution 5, let stand for 30min, take out the catalyst and blow it with 2MPa air knife, then treat it in a 100℃ oven for 12 hours, and calcine it at 550℃ for 6 hours. Then reduce it at 400℃ for 5 hours in 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst containing TS-1 titanium silicon molecular sieve coating. Among them, the coating particle size is between 380-550nm, the mesopore channel size distribution is 13-14nm, and the specific surface area is 550m 2 / g, and the powder loss rate of the coating is 0.4%.
[0149] The SEM and TEM images of the monolithic catalyst containing the TS-1 titanium silicon molecular sieve coating are shown in Figures 1 and 2. Figure 1 and Figure 2 shown.
[0150] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1, reaction pressure 0.1MPa, reaction temperature 315℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 300h (i.e., the reaction was carried out continuously for 300h, and the catalytic activity of the catalyst did not decrease significantly).
[0151] Example 7
[0152] This example is used to illustrate the monolithic catalyst containing TS-1 molecular sieve coating and its preparation method and application.
[0153] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0154] Secondly, 3.6 g of isopropanol and 0.368 g of n-butyl titanate were mixed evenly to obtain solution 1. 55.8 g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58 g of ethyl orthosilicate and 6.9 g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.05 ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 1 hour, and then heated to 50°C at a rate of 5-6°C / min, and alcohol was removed at 50°C for 12 hours to obtain transparent gel liquid 4. The transparent gel liquid 4 was mixed with 1 g of commercially available TS-1 seed crystals and 0.5 g of P123 at 40°C and stirred for 1 h to obtain a coating slurry. The coating slurry was then added dropwise to the acid-treated cordierite honeycomb ceramics, transferred to an autoclave, and crystallized at 170°C for 36 h. After being taken out, washed and dried, it was calcined in an air atmosphere at 550°C for 6 hours to obtain a cordierite honeycomb ceramic containing a TS-1 molecular sieve coating.
[0155] Take 0.5L 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) and stir for 3h at 25℃, pH=9 to obtain active component solution 5. The cordierite honeycomb ceramic containing TS-1 molecular sieve coating is immersed in active component solution 5, let stand for 30min, take out the catalyst and blow it with 2MPa air knife, then treat it in a 100℃ oven for 12 hours, and calcine it at 250℃ for 6 hours. Then reduce it at 400℃ for 5 hours in 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst containing TS-1 titanium silicon molecular sieve coating. Among them, the coating particle size is between 300-400nm, the mesopore channel size distribution is 10-15nm, and the specific surface area is 280m 2 / g, and the powder loss rate of the coating is 0.3%.
[0156] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 295℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 350h (i.e., the reaction was carried out continuously for 350h, and the catalytic activity of the catalyst did not decrease significantly).
[0157] Example 8
[0158] This example is used to illustrate the monolithic catalyst containing TS-1 molecular sieve coating and its preparation method and application.
[0159] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 0.5 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0160] Secondly, 3.6 g of isopropanol and 0.368 g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9 g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58 g of ethyl orthosilicate and 6.9 g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01 ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. The transparent gel liquid 4 was mixed with 1 g of commercially available TS-1 seed crystals and 0.5 g of P123 at 40°C and stirred for 1 h to obtain a coating slurry. The coating slurry was then added dropwise to the acid-treated cordierite honeycomb ceramics, transferred to an autoclave, and crystallized at 170°C for 36 h. After being taken out, washed and dried, it was calcined in an air atmosphere at 550°C for 6 hours to obtain a cordierite honeycomb ceramic containing a TS-1 molecular sieve coating.
[0161] Take 0.5L 1mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) and stir for 3h at 25℃, pH=9 to obtain active component solution 5. The cordierite honeycomb ceramic containing TS-1 molecular sieve coating is immersed in active component solution 5, let stand for 30min, take out the catalyst and blow it with 2MPa air knife, then treat it in a 100℃ oven for 12 hours, and calcine it at 550℃ for 6 hours. Then reduce it at 200℃ for 5 hours in 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst containing TS-1 titanium silicon molecular sieve coating. Among them, the coating particle size is between 80-150nm, the mesopore channel size distribution is 3-4nm, and the specific surface area is 550m 2 / g, and the powder loss rate of the coating is 0.6%.
[0162] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 285℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 160h (i.e., the reaction was carried out continuously for 160h, and the catalytic activity of the catalyst did not decrease significantly).
[0163] Example 9
[0164] This example is used to illustrate the monolithic catalyst containing TS-1 molecular sieve coating and its preparation method and application.
[0165] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0166] Secondly, 3.6 g of isopropanol and 0.368 g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9 g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58 g of ethyl orthosilicate and 6.9 g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01 ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. The transparent gel liquid 4 was mixed with 1 g of commercially available TS-1 seed crystals and 0.5 g of P123 at 40°C and stirred for 1 h to obtain a coating slurry. The coating slurry was then added dropwise to the acid-treated cordierite honeycomb ceramics, transferred to an autoclave, and crystallized at 170°C for 36 h. After being taken out, washed and dried, it was calcined in an air atmosphere at 550°C for 6 hours to obtain a cordierite honeycomb ceramic containing a TS-1 molecular sieve coating.
[0167] Take 0.5L 2mol / L chloroplatinic acid, palladium chloride mixed solution (platinum-palladium molar ratio of 1:1) and 200ml 1mol / L zirconium nitrate, ferric nitrate mixed solution (zirconium-iron molar ratio of 1:1) and stir for 3h at 25℃, pH=9 to obtain active component solution 5. The cordierite honeycomb ceramic containing TS-1 molecular sieve coating is immersed in active component solution 5, let stand for 30min, take out the catalyst and blow it with 2MPa air knife, then treat it in a 100℃ oven for 12 hours, and calcine it at 250℃ for 6 hours. Then reduce it at 400℃ for 5 hours in 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst containing TS-1 titanium silicon molecular sieve coating. Among them, the coating particle size is between 80-150nm, the mesopore channel size distribution is 3-4nm, and the specific surface area is 550m 2 / g, and the powder loss rate of the coating is 0.1%.
[0168] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 325℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 300h (i.e., the reaction was carried out continuously for 300h, and the catalytic activity of the catalyst did not decrease significantly).
[0169] Example 10
[0170] This example is used to illustrate the monolithic catalyst containing TS-1 molecular sieve coating and its preparation method and application.
[0171] First, a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic was treated with 2 mol / L nitric acid at 80° C. reflux for 24 h, washed with deionized water until the pH value was 7, and dried naturally for later use.
[0172] Secondly, 3.6 g of isopropanol and 0.368 g of n-butyl titanate were mixed evenly to obtain solution 1. 27.9 g of tetrapropylammonium hydroxide was placed in a beaker, and 22.58 g of ethyl orthosilicate and 6.9 g of H2O were added and stirred for 30 minutes to obtain solution 2. Solution 1 was added to solution 2 at a rate of 0.01 ml / min, and stirred for 3 hours to obtain mixed solution 3. Mixed solution 3 was aged at room temperature for 3 hours, and then heated to 90°C at a rate of 5-6°C / min, and alcohol was removed at 90°C for 12 hours to obtain transparent gel liquid 4. The transparent gel liquid 4 was mixed with 1 g of commercially available TS-1 seed crystals and 0.5 g of P123 at 40°C and stirred for 1 h to obtain a coating slurry. The coating slurry was then added dropwise to the acid-treated cordierite honeycomb ceramics, transferred to an autoclave, and crystallized at 170°C for 36 h. After being taken out, washed and dried, it was calcined in an air atmosphere at 550°C for 6 hours to obtain a cordierite honeycomb ceramic containing a TS-1 molecular sieve coating.
[0173] Take 0.5L 1mol / L hexahydroxyplatinic acid (IV) 2-hydroxyethylamine salt, palladium acetate mixed solution (platinum-palladium molar ratio of 1:1) and 200ml 1mol / L cerium nitrate, lanthanum nitrate mixed solution (cerium-lanthanum molar ratio of 1:1) and stir for 3h at 55℃, pH=11 to obtain active component solution 5. The cordierite honeycomb ceramic containing TS-1 molecular sieve coating is immersed in active component solution 5, let stand for 30min, take out the catalyst and blow it with 2MPa air knife, then treat it in a 100℃ oven for 12 hours, and calcine it at 450℃ for 6 hours. Then reduce it at 700℃ for 3 hours in 10% H2, 90% N2 atmosphere to obtain a monolithic catalyst containing TS-1 titanium silicon molecular sieve coating. Among them, the coating particle size is between 80-150nm, the mesopore channel size distribution is 3-4nm, and the specific surface area is 550m 2 / g, and the powder loss rate of the coating is 0.1%.
[0174] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 305℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 150h (i.e., the reaction was carried out continuously for 150h, and the catalytic activity of the catalyst did not decrease significantly).
[0175] Comparative Example 1
[0176] The monolithic catalyst containing TS-1 molecular sieve coating was prepared according to the method of Example 1, except that the cordierite honeycomb ceramic was not subjected to acid treatment, and the coating slurry was directly added to the cordierite honeycomb ceramic to prepare the cordierite honeycomb ceramic containing TS-1 molecular sieve coating, thereby finally preparing the monolithic catalyst D1 containing TS-1 titanium silicon molecular sieve coating, wherein the coating particle size is between 80-150nm, the mesopore size distribution is 3-4nm, and the specific surface area is 550m 2 / g, and the powder loss rate of the coating is 4.7%.
[0177] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 265℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that the CO concentration was about 1000ppm, the VOCs concentration was about 250ppm, the conversion rate was 97.5%, and the catalyst stability was 50h.
[0178] Comparative Example 2
[0179] Based on Example 1, the difference is that the coating slurry is prepared according to the following process:
[0180] 50g of TS-1 molecular sieve (purchased from Shanghai Zhuoyue Chemical Technology Co., Ltd., Na type, with a micropore size distribution of 0.5-0.65nm) was mixed with 100g of deionized water and wet ball milled to obtain a coating slurry. Thus, a monolithic catalyst D2 containing a TS-1 titanium silicon molecular sieve coating was finally obtained, wherein the coating particle size was between 80-150nm, the mesopore size distribution was 3-4nm, and the specific surface area was 500m 2 / g, and the powder loss rate of the coating is 2.8%.
[0181] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000 h -1 , reaction pressure 0.1MPa, reaction temperature 275℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO concentration was about 800ppm, VOCs concentration was about 200ppm, conversion rate was ≥98%, and catalyst stability was 100h.
[0182] It can be seen from the above examples and comparative examples that the monolithic catalyst containing titanium silicon molecular sieve coating prepared by the present invention exhibits good catalytic effect in the process of catalytic oxidation of carbon-based oxygen-containing molecular gas, and the catalyst stability is significantly better, suitable for continuous long-term operation.
[0183] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A monolithic catalyst containing a titanium silicon molecular sieve coating, characterized in that: The monolithic catalyst comprises: A carrier, wherein the carrier is a regular carrier treated with acid; A coating layer attached to the carrier, wherein the coating layer is a titanium silicon molecular sieve; and an active component dispersed in the coating, the active component comprising a noble metal and optionally an alloying metal; The powder loss rate of the coating is below 1%, preferably 0.1-1%.
2. The monolithic catalyst containing titanium silicon molecular sieve coating according to claim 1, characterized in that: The particle size of the coating is 50-500nm; Preferably, the mesoporous channel size of the coating is 1-50 nm, and the specific surface area is 300-600 m 2 / g.
3. The monolithic catalyst containing titanium silicon molecular sieve coating according to claim 1 or 2, characterized in that: Relative to 100 parts by weight of the carrier, the content of the coating layer is 1-10 parts by weight, and the content of the active component is 0.1-1 part by weight.
4. The monolithic catalyst containing titanium silicon molecular sieve coating according to claim 1, characterized in that: The structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
5. The monolithic catalyst containing titanium silicon molecular sieve coating according to any one of claims 1 to 4, characterized in that: In the active component, the molar ratio of the noble metal to the alloy metal is 1:0.1-0.
3.
6. The monolithic catalyst containing titanium silicon molecular sieve coating according to claim 1 or 5, characterized in that: The noble metal is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium.
7. The monolithic catalyst containing titanium silicon molecular sieve coating according to claim 1 or 5, characterized in that: The alloy metal is at least one of Fe, La and Ce, and is preferably a combination of La and Ce.
8. The monolithic catalyst containing titanium silicon molecular sieve coating according to any one of claims 1 to 7, characterized in that: The titanium silicate molecular sieve is TS-1 molecular sieve.
9. A method for preparing a monolithic catalyst containing a titanium silicon molecular sieve coating, characterized in that: The method comprises the following steps: (1) treating the structured support with acid; (2) mixing the alcohol solution of the titanium source with the aqueous solution containing the microporous template and the silicon source, aging, removing the alcohol, and then mixing the obtained gel solution with titanium silicon molecular sieve seed crystals and the mesoporous template to obtain a coating slurry; (3) adding the coating slurry to the acid-treated regular carrier, followed by crystallization, washing, drying and calcination to obtain a carrier containing the coating; (4) impregnating the coated support into a mixed solution containing a noble metal precursor and an optional structural additive, and then sequentially drying, calcining and reducing the impregnated catalyst precursor.
10. The method according to claim 9, characterized in that In step (1), the acid treatment process includes: using an acidic solution to reflux the structured carrier, then washing it to neutrality and drying it; Preferably, the concentration of the acidic solution is 1-3 mol / L; Preferably, the acid in the acidic solution is at least one of nitric acid, sulfuric acid and hydrochloric acid; Preferably, the conditions of the reflux treatment include: a temperature of 70-90° C. and a time of 12-36 hours; Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
11. The method according to claim 9, characterized in that In step (2), the specific process of mixing the alcohol solution of the titanium source with the aqueous solution containing the microporous template and the silicon source is: adding the alcohol solution of the titanium source to the aqueous solution containing the microporous template and the silicon source at a rate of 0.005-0.015 mL / min, stirring and mixing for 2-5 hours; Preferably, the titanium source is selected from at least one of tetraalkoxytitanium, tetraalkyl titanate and titanium tetrachloride; Preferably, the microporous template is selected from at least one of tetrapropylammonium hydroxide, tetrapropylammonium bromide and tetraethylammonium hydroxide; Preferably, the silicon source is selected from at least one of silicate, silicic acid, silica hydrogel and tetraethyl orthosilicate; Preferably, the titanium silicon molecular sieve seed crystal is a TS-1 molecular sieve seed crystal; Preferably, the mesoporous template agent is selected from at least one of P123, CTAB and n-butylamine.
12. The method according to claim 9, characterized in that In step (3), the crystallization conditions include: temperature of 150-200°C and time of 10-72h; Preferably, the calcination conditions include: a temperature of 400-650° C. and a time of 4-10 hours.
13. The method according to any one of claims 9 to 12, characterized in that: In step (4), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12; Preferably, the noble metal precursor is selected from at least one of chloroplatinic acid, hexahydroxoplatinic acid (IV) 2-hydroxyethylamine salt, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate; Preferably, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide; Preferably, the calcination conditions include: a temperature of 300-400°C and a time of 4-10 hours; Preferably, during the reduction process, the reducing atmosphere is H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations; Preferably, the reduction conditions include: catalyst heating rate of 2-20°C / min, reduction temperature of 300-450°C, and reduction time of 1-10h.
14. An integral catalyst containing a titanium silicon molecular sieve coating prepared by the method according to any one of claims 9 to 13.
15. Use of the monolithic catalyst containing titanium silicon molecular sieve coating according to any one of claims 1 to 8 and 14 in catalytic oxidation of carbon-based oxygen-containing molecular gas.
Citation Information
Patent Citations
Metallic oxide mixture catalyzer for purifying organic waste gas and method of preparing the same
CN101138728A
Oxidation catalyst and method for destruction of co, voc and halogenated voc
CN102481549B
Catalytic combustion catalyst and preparing method thereof
CN1488435A
Automobile exhaust gas purifying process
CN1986035A
Honeycomb-ceramic-type monolithic catalyst, and preparation method and application thereof
CN102133537A
Cited By
Molecular sieve based photoelectric positive electrode, preparation method thereof and photo-assisted near-neutral zinc air battery
CN120149430A